Case Report: Thalidomide in the treatment of complicated central nervous system tuberculosis - Liu, Ping; Li, Tao; Xi, Xiuhong; Pei, Ning; Huang, Wei; Liu, Xuhui; Xia, Lu; Yang, Yang; Lu, Shuihua (Frontiers in Tropical Diseases, 2022)
Central nervous system tuberculosis (CNSTB) is the most fatal type of tuberculosis (TB). Early administration of glucocorticoids can improve the prognosis of patients and reduce mortality; however, some patients do not respond well to anti-tuberculosis drugs and glucocorticoids. Thalidomide is an immunomodulatory drug that has been used in the treatment of TB. We retrospectively reviewed the drug to describe its clinical characteristics, efficacy, and safety in the treatment of four complicated CNSTB patients who responded well to thalidomide. Thalidomide may be an effective and well-tolerated drug for the treatment of CNSTB, and requires further study.